Initial prospective study of ambulatory mPCNL on upper urinary tract calculi - Tian, Ye; Yang, Xiushu; Luo, Guangheng; Wang, Yandong; Sun, Zhaolin (Urology Journal, 2020)
Objective: To explore the feasibility and safety of ambulatory mPCNL (mini percutaneous nephrolithotomy) on upper urinary tract calculi. Methods: Clinical data of 18 patients received ambulatory mPCNL during Aug. 2017 to Jan. 2018 and 23 patients treated with routine inpatient mPCNL of the corresponding period were collected. All the patients included received 16Fr channel PCNL under the guidance of Doppler ultrasound. A 6Fr double J stent was placed in the ureter for internal drainage, and either an indwelling 14Fr open nephrostomy tube was placed or the puncture channel was filled with absorbable hemostatic materials alone, depends on the bleeding condition of the puncture channel and the intraoperative conditions. Preoperative parameters and surgery time, complications, total hospitalization costs and hospital stay time between the two groups were compared. Results: Preoperative parameters regarding age (P=0.057), sex distribution (P=0.380), ASA score (P=0.388), Calculi CT value (P=0.697), and the S.T.O.N.E. score (P=0.122) were comparable between the two groups. Maximum diameter of calculi (cm) of the conventional hospitalization group, however, was larger than the ambulatory surgery group (P=0.041). There were no significant differences in the mean surgery time (P=0.146), postoperative hemoglobin drop (P=0.865), Calculi-free rate on the next day after surgery (P=0.083) and postoperative fever rate (P=0.200) between the two groups. With regard to tubeless rate (P<0.001), total hospitalization costs (P=0.003) and hospital stay time (P<0.001), there were significant advantage favored ambulatory mPCNL. Conclusions: For patients with simple upper urinary tract calculi and relatively good performance status, ambulatory mPCNL is feasible as it’s equally safe and efficient as compared with routine inpatient mPCNL. Moreover, ambulatory mPCNL decreases hospitalization costs and hospital stay time. Nevertheless, perioperative management should be carefully conducted, and well-designed studies are warranted.